Arah Pendidikan Pesantren - Madarik, Muhammad; Puadi, Hairul (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2022)
The existence of Islamic boarding schools in Indonesia is quite familiar to Indonesian citizens. The special characteristics of Islamic boarding schools are the curriculum that is focused on religious sciences integrally, for example Arabic syntax, Arabic morphology, Islamic law, Islamic jurisprudence system, Hadith, interpretation of Al-Qur'an, Islamic theology, Sufism, and rhetoric. The pesantren education system often characterized: [a] the use of traditional system, [b] the spirit of democracy, [c] A system that prioritizes simplicity, and [e] A system that does not suffer from symbolic disease. There are several traditions of santri which can be identified as social values, such as [a] Volunteering (sincere) and serving (khidmah), [b] Wise, [c] Simplicity, [d] Collective, [e] Organizing joint activities, [f] Guided freedom, [g] Independent, and [h] Make boarding schools a place to gain knowledge and dedication. The internalization of modernization (reorientation) of education in pesantren cannot be separated from the supporting and challenging factors. However, as a moderate Islamic education system, pesantren must take the following steps: [a] advancing the educational paradigm, [b] Islamic education being developed towards an ideological-sociological perspective, [c] Restore the basic curriculum framework and map out the basics of discussion, and [d] interpreting according to social reality.